A Novel High Speed Phase-Locked Loop For Communication System - Munmee Borah, Tulshi Bezboruah (International Journal of Advanced Science and Technology, 2020)
In this paper we present a simulation study by considering the behavioral modeling aspects of a novel phase - locked loop of order four. The study is carried out to speed up the settling time for communication system during acquisition. The model utilizes active lag-lead filter and the filter in standard feedback approaches in the loop for the study. The linear analysis of the model is carried out through the evaluation of s - domain transfer functions. The MATLAB platform is deployed to carry out the simulation and the evaluation is done to observe the stability as well as the transient behavior of the model. The study shows that the settling time metrics for the model by consideringstandard feedback approach is observed to be faster than the approach of active lag lead filter. Also, the standard feedback approach gives better stability in terms of phase margin. The minimum overshoot recorded with standard feedback approach and active lag - lead filters are 0% and 0.9127% respectively. From the analysis of the proposed high speed phase - locked loop models it can be concluded that the model with the filter of standard feedback approaches in the loop can enhance the switching speed up to 0.193ns which is the novelty of the system.